On-Chip Broadband Mid-Infrared Supercontinuum Generation Based on Highly Nonlinear Chalcogenide Glass Waveguides - Xia, Di; Huang, Yufei; Zhang, Bin; Yang, Zelin; Zeng, Pingyang; Shang, Haiyan; Cheng, Huanjie; Liu, Linghao; Zhang, Mingjie; Zhu, Ying; Li, Zhaohui (Frontiers in Physics, 2021)
On-chip mid-infrared (MIR) supercontinuum generation (SCG) covering the molecular functional spectral region (3-12 μm) offers the advantages of robustness, simplicity and compactness. Yet, the spectral range still can’t be expanded beyond 10 μm. In this paper, on-chip ultrabroadband MIR SCG in a high numerical aperture chalcogenide (ChG) waveguide is numerically investigated. The ChG waveguide consisting of a Ge-As-Se-Te core and a Ge-Se upper and lower cladding is designed to optimize the nonlinear coefficients and dispersion profile. By assisting with dispersive wave generation in both short and long-wavelength range, broadband SCG ranging from 2 to 13 µm is achieved. Besides, a fabrication scheme is proposed to realize the precise manipulation of dispersion design. Such results demonstrate that such sources are suitable for compact, chip-integrated molecular spectroscopy applications.